Response Time pada Penggunaan AdGuard Home di Container Mikrotik - Rizky Bagus Pratama; Dian Widiyanto Chandra (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
DNS-based ad blocking is used to increase website access efficiency by reducing unnecessary elements. This research analyzes the effect of using AdGuard Home in the MikroTik container on response time, delay and data transfer when accessing website. This research used an experimental method, with 30 tests before and after the implementation of AdGuard Home. Google DevTools was used to measure response time and data transfer , while Wireshark was used to measure delay. The results show that response time decreased by 36.38% from 78.46 ms to 49.91 ms, and data transfer decreased by 42.25% from 7.1 MB to 4.1 MB, indicating an increase in network efficiency. However, the delay increased by 12.3% from 256.9 ms to 288.5 ms, due to additional latency in the DNS filtering process. Thus, this research proves that AdGuard Home in the MikroTik container can increase website access efficiency by speeding up response time and reducing data transfer , but increasing delay. Further optimization is needed to reduce the impact of delays to maintain an optimal user experience.